Chemical and Isotopic Characteristics of Groundwater from Deep Sandstone Aquifer in Northern Anhui Province, China: A Case Study - Sun, L.H.; Gui, H.R. (Asian Journal of Chemistry, 2014)
For evaluating the hydro-chemical and isotopic contents of groundwater, eight samples from the a deep sandstone aquifer in Qianyingzi coal mine, northern Anhui Province, China have been collected for analyzing major ion concentrations and stable isotopic (hydrogen and oxygen) contents. Two water types were recognized: Na-HCO3 and Na-SO4. In comparison with the drinking water standards of World Health Organization, only Ca2+, Mg2+ and Cl– concentrations can meet the demand. Correlations between ions imply that chemical compositions of the groundwater was controlled by multi processes i.e. dissolution of evaporate, weathering of silicate minerals and cation exchange. The stable isotopic contents of the groundwater samples from the sandstone aquifer is similar to the shallow groundwater and limited in a narrow range, indicating that the aquifer is independent relative to other aquifers and, the groundwater in the aquifer was recharged by paleo-precipitation, which was modified by the processes during penetration from surface to the aquifer or the water rock interaction during the long residence time in the aquifer, rather than the sealed up water during sedimentation.